2022
DOI: 10.21203/rs.3.rs-1895068/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Administrative Burden Associated with Cost-Related Delays in Care in U.S. Cancer Patients

Abstract: Purpose: U.S. cancer patients engage in a range of administrative tasks to pay for their healthcare (e.g., estimating costs, negotiating with insurers, and making sense of bills). This study investigates the relationship between payment tasks and timely access to cancer care. Methods: We administered a web-based survey to 510 cancer patients and survivors, stratified by cancer type and geographic region, to assess their financial and insurance concerns and experiences. Logistic regression was used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…To our knowledge, this study is the first to ask oncology patients about their experience with PA. Understanding the patient perspective is a vital component of efforts to refine the PA process, given that patients (and their families) are ultimately financially responsible for resultant medical bills and often must take on the administrative burdens of PA while simultaneously managing the physical and psychosocial effects of their disease and treatment . Prior studies have suggested that additional burdens are associated with delayed or forgone care and are more likely to affect those who are already at risk for compromised or fractured care, including Black or African American, disabled, female, and low-income patients . Research also shows that PA may place disproportionate limitations to access on vulnerable populations, patients of Asian descent, and those with Medicare Advantage plans .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this study is the first to ask oncology patients about their experience with PA. Understanding the patient perspective is a vital component of efforts to refine the PA process, given that patients (and their families) are ultimately financially responsible for resultant medical bills and often must take on the administrative burdens of PA while simultaneously managing the physical and psychosocial effects of their disease and treatment . Prior studies have suggested that additional burdens are associated with delayed or forgone care and are more likely to affect those who are already at risk for compromised or fractured care, including Black or African American, disabled, female, and low-income patients . Research also shows that PA may place disproportionate limitations to access on vulnerable populations, patients of Asian descent, and those with Medicare Advantage plans .…”
Section: Discussionmentioning
confidence: 99%
“… 19 Prior studies have suggested that additional burdens are associated with delayed or forgone care and are more likely to affect those who are already at risk for compromised or fractured care, including Black or African American, disabled, female, and low-income patients. 20 , 21 Research also shows that PA may place disproportionate limitations to access on vulnerable populations, patients of Asian descent, and those with Medicare Advantage plans. 22 , 23 , 24 Dealing with PA issues adds an extra layer of stress, which is known to increase anxiety and can worsen treatment-related and disease-related symptoms and adverse effects.…”
Section: Discussionmentioning
confidence: 99%